Estruturas cristalinas e moleculares de indóis 1,3- substituídos - Wulf, Glaudeston Dutra (2012)
This work consists of 7 chapters. In Chapter 1 a description of the problems addressed here are presented, starting with a brief story about the development of Xray diffraction crystallography, starting with the description of crystals, unit cells and, cocristals and at the end the concepts of supramolecular chemistry and crystal engineering, together with the description of the compounds studied and an application of the use of computational studies complementing the crystalochemical studies, are presented. In chapter 2 the objectives of this work are described. The third chapter includes the experimental procedures that have been used to determine the molecular and crystal structures, as well as the ones used for the modeling studies performed. In Chapter 4 the results are described and discussed, that is, the crystal structures of two 1,3-substituted indoles: 3-Ethenyl-1-(4- methylphenylsulfonyl)-1H-indole (compound 1) and 3-Formyl-1-(4- methylphenylsulfonyl)-1H-indole (compound 2). The striking result is that both compounds have two independent molecules in the asymmetric unit, in other words, Z' > 1. Both molecules of compound 1 are very similar and that of compound 2 they are rotamers. Molecular modeling calculations showed that in all cases the independent molecules have almost the same energy and that the rotational barrier for interconversion between rotamers is between 2.0 and 3.0 kcal.mol-1. Due to this low energy barrier, both conformers should coexist in solution and when crystallization occurs, they have the same probability to crystallize. Chapter 5 presents the conclusions of this study. In chapter 6 the references are given and, in Chapter 7 a copy of the published paper can be found.